Analysis of a Benzamide/Cholesterol Mixture by Using TLC/FTIR Technique. (10th December 2013) - Fan, Xiaokun; Guo, Ran; Shi, Jia-jia; Wu, Haijun; He, Anqi; Wei, Yongju; Liu, Cuige; Weng, Shifu; Yang, Zhanlan; Xu, Yizhuang; Noda, Isao; Wu, Jinguang
Abstract : We applied TLC/FTIR coupled with a mapping technique to analyze a cholesterol/benzamide mixture. Narrow-band TLC plates by using AgI as a stationary phase were used to separate benzamide and cholesterol. The distribution of cholesterol and benzamide spots was manifested by 3D chromatogram. Benzamide and cholesterol can be successfully separated by the narrow-band TLC plate. Moreover, characteristic bands of benzamide and cholesterol can be identified from their FTIR spectra. In addition, the FTIR spectra of the separated benzamide and cholesterol spots on the narrow band TLC plate are roughly the same as the corresponding reference IR spectra.